Indispensable Innovations in an English Listening and Speaking Class at an E-Learning Training System at Ho Chi Minh Open University (HOU) - Bich, Tuyen Nguyen Chau (International Journal on Open and Distance e-Learning, 2016)
The core value of the e–learning training system at Ho Chi Minh Open University (HOU) is being open to all learners who are interested in developing their knowledge, sharpening their practical skills under flexible learning conditions, and following quality training procedures. In some learning environments, e-learning courses using web-based learning, online exercises, media broadcast lectures, and the like are applied to encourage learners to access knowledge and promote improved learning performances. However, in English listening and speaking classes, learners with strong preferences, interests, determination, and personalization mechanisms can attain great achievements, but the rest do not perform at a high level. Hence, to improve the quality of this training model and meet the preferences and requirements of the learners, a survey questionnaire was administered to 120 sophomores in two listening and speaking classes at HOU. The results show that most learners expect some indispensable innovations, including increasing the class time to help learners gain more confidence and sociolinguistic competence in speaking in the target language; providing supplementary online exercises to support learner autonomy and improvement of listening skill; and maintaining the teacher-learner relationship to provide learners with opportunities for consultation and assessment.